1994
DOI: 10.1007/bf01704699
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for infection byPseudomonas aeruginosa in patients with ventilator-associated pneumonia

Abstract: patients with VAP and these factors have a greater risk of infection by Ps. aeruginosa and empirical therapy for these episodes should include anti-pseudomonal activity until etiologic diagnosis is established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
4
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(76 citation statements)
references
References 21 publications
6
61
4
5
Order By: Relevance
“…1,2 P. aeruginosa can become invasive when the first barrier of immune defense fails, for example, when the body surface becomes disrupted. High-risk groups for acquisition of P. aeruginosa include long-term hospitalized patients in intensive care units, burn victims, patients undergoing mechanical ventilation (ventilator-associated pneumonia), and immunocompromised individuals with diabetes, neutropenia, cancer, and post transplantation surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 P. aeruginosa can become invasive when the first barrier of immune defense fails, for example, when the body surface becomes disrupted. High-risk groups for acquisition of P. aeruginosa include long-term hospitalized patients in intensive care units, burn victims, patients undergoing mechanical ventilation (ventilator-associated pneumonia), and immunocompromised individuals with diabetes, neutropenia, cancer, and post transplantation surgery.…”
Section: Introductionmentioning
confidence: 99%
“…High-risk groups for acquisition of P. aeruginosa include long-term hospitalized patients in intensive care units, burn victims, patients undergoing mechanical ventilation (ventilator-associated pneumonia), and immunocompromised individuals with diabetes, neutropenia, cancer, and post transplantation surgery. 2,3 P. aeruginosa is a leading cause of nosocomial infections and is responsible for 10% of hospital acquired infections. 4 Prevention of airway infections with P. aeruginosa is also a major goal in the treatment of cystic fibrosis patients 5 and several studies indicate that colonization of the lower airways of COPD by P. aeruginosa is associated with enhanced airway inflammation, and probably has deleterious consequences on the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that sampling only the segment showing purulent secretions results in an increase in sensitivity [26] but histological studies [37,38] report that VAP is a multifocal process; therefore a broad sampling Push the inner cannula of the PSB to eject the polyethylene glycol plug. 4 Wedge the brush in the subsegmental area or sample secretions if these are visualized. 5 Retract the brush into the inner cannula and the inner cannula into the outer cannula, and remove the PSB from the bronchoscope 6…”
Section: Bronchoscopic Techniquesmentioning
confidence: 99%
“…3 After the injection of each aliquot, gently aspirate through the suction channel. 4 Keep the ®rst aliquot for separate analysis.…”
Section: Open Lung Biopsy Although Open Lung Biopsy (Olb)mentioning
confidence: 99%
See 1 more Smart Citation